'New Forces': How Classroom Textbooks Are Redefining Journalism. (March 2023) - Coatney, Caryn
Educators increasingly need to teach journalism within everchanging digital newsrooms. This study conducts a rare analysis of popular, United States–focused textbooks to answer a foundational question: What is journalism? Drawing on concepts of journalism's social function, this analysis finds the university textbooks are providing more upbeat messages, but significantly different definitions. General textbooks often emphasize a dominant, print-oriented watchdog role, while specialized books mostly accentuate journalists' neighborly, multimedia approach to reporting everyday life. This study points to the value of providing pluralist journalism approaches that show varied views of journalists' moral authority in reporting for diverse audiences.